Do highly ornamented and less parasitized males have high quality sperm? – an experimental test for parasite‐induced reproductive trade‐offs in European minnow (Phoxinus phoxinus). Issue 22 (21st October 2014) - Kekäläinen, Jukka; Pirhonen, Juhani; Taskinen, Jouni
<x xml:space="preserve">Abstract</x> We investigated parasite‐induced reproductive trade‐offs in the European minnow (Phoxinus phoxinus). Experimental infection with non‐specific fish parasite, glochidia larvae of duck mussel (Anodonta anatina) reduced the curvature of the sperm swimming trajectory and number of breeding tubercles, but did not affect sperm motility or expression of male colour ornamentation. Our results indicate that although glochidia infection may impair male reproductive success, it may not create strong trade‐off between breeding colouration and sperm quality. <boxed-text content-type="graphic" id="ece31267-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>